Interlingual Translation Quality Via Artificial Intelligence (Conference on English Language Teaching, 2025)
Artificial intelligence is so important to interlingual translation, nowadays. One of the translation machines that is currently trending among today's translation learners is a translation made by a giant company called Google with its product, Google Lens. Google Lens will help you translate interlingually using a smartphone connected to the internet and then in real time translate the text taken from the smartphone photo in the source language into the target language that is optionally selected according to the user's needs. this study examines the quality of interlingual translation using artificial intelligence from Google, known as Google Lens, which is capable of translating using a photography feature. This research is the quantitative which related to data measured with numerical symbols carried out using descriptive statistic. The conclusion is that the translation machine from the artificial intelligence-based translation machine by photographing Acehnese text into Indonesian needs to be further refined, especially to be more accurate, acceptable, and readable.